Impact of doppler ultrasound on the clinical and andrological stallions examination (Research, Society and Development, 2021)
This study aimed to evaluate the association of Doppler ultrasound with clinical andrological examination to identify the reproductive quality of stallions in paraiban swamp region. Eleven horses were used, aged between three and 27 years. The ejaculates were collected by the artificial vagina method and the seminal samples were submitted to field evaluation (subjective motility, cellular integrity) and in the laboratory (objective motility, cellular integrity). After seminal collection, the animals were submitted to testicular blood flow evaluation with Doppler ultrasound. Differences (P